2010
DOI: 10.1002/ctpp.201010031
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Model Moderately Coupled Plasmas

Abstract: We review our approach to the modelling of optical properties of model moderately coupled plasmas. On the basis of the classical theory of moments the external and internal dynamic conductivities and the reflectivity coefficient of a model hydrogen moderately coupled plasma are determined using all known exact relations and sum rules. The sum rules which are the power frequency moments of the loss function are calculated using the Deutsch effective potential and the hypernetted chain equations. MD simulation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The thermodynamical functions of the hydrogen plasma have been evaluated and comparison with some theoretical and simulation data has shown that the proposed effective potential is adequate for determination of static plasma characteristics. It is worthwhile mentioning that further progress can be achieved for calculation of the plasma optical properties [21] and its polarizational stopping power [22].…”
Section: Discussionmentioning
confidence: 99%
“…The thermodynamical functions of the hydrogen plasma have been evaluated and comparison with some theoretical and simulation data has shown that the proposed effective potential is adequate for determination of static plasma characteristics. It is worthwhile mentioning that further progress can be achieved for calculation of the plasma optical properties [21] and its polarizational stopping power [22].…”
Section: Discussionmentioning
confidence: 99%